Subtle Deficits in Instrumental Activities of Daily Living in Subtypes of Mild Cognitive Impairment - Teng, Edmond (S. Karger AG, 2010)
BACKGROUND/AIMS: Greater cognitive and functional deficits in mild cognitive impairment (MCI) are associated with higher rates of dementia. We explored the relationship between these factors by comparing instrumental activities of daily living (IADLs) among cognitive subtypes of MCI and examining associations between IADL and neuropsychological indices. METHODS: We analyzed data from 1,108 MCI and 3,036 normal control subjects included in the National Alzheimer's Coordinating Center Uniform Data Set who were assessed with the Functional Activities Questionnaire (FAQ). RESULTS: IADL deficits were greater in amnestic than nonamnestic MCI, but within these subgroups, did not differ between those with single or multiple domains of cognitive impairment. FAQ indices correlated significantly with memory and processing speed/executive function. CONCLUSIONS: IADL deficits are present in both amnestic MCI and nonamnestic MCI but are not related to the number of impaired cognitive domains. These cross-sectional findings support previous longitudinal reports suggesting that cognitive and functional impairments in MCI may be independently associated with dementia risk.